Risk factors of musculoskeletal symptoms among healthcare workers in a public hospital - Abd. Rahman, Siti Hasrina; Rasdi, Irniza; Karrupiah, Karmegam; Abdullah, Abdul Mujid (Universiti Putra Malaysia, 2021)
Introduction: This study aims to determine the risk factors of musculoskeletal symptoms (MSS) among healthcare workers in a public hospital. Methods: This cross-sectional study involved 121 respondents among healthcare workers (HCW) (doctors, nurses and physiotherapists) working in Emergency and Trauma Department and Physiotherapy Department in a public hospital by using universal sampling. Self-administered questionnaire containing questions on socio demographical data, work characteristics, body movement and work tasks, Standardized Nordic Questionnaire for assessing musculoskeletal symptoms and Job Content Questionnaire (JCQ) for measuring psychosocial risk factors was used as the main instrument for this study. Results: Response rate was 81.88% and 95% of respondents reported to have at least one symptom at body site. The most prevalent symptom was neck pain (80.2%) followed by low back pain (79.3%), and shoulder pain (71.9%). Physiotherapists reported to have more symptoms of MSS than doctors and nurses (χ2 = 6.84, p = 0.033). For socio-demographic characteristics, only level of education had significant association with MSS (χ2 = 7.25, p = 0.008). Meanwhile, there were 14 body movements and work tasks had significant association (moderate) with MSS. For psychosocial risk factors, high job insecurity was significantly (fair) correlated with more MSS (r=-0.302). Conclusion: The prevalence of reported MSS at a number of body sites was high which were associated with socio-demographic background, work task characteristics, body movements and work tasks, and psychosocial risk factors.